Optimizing rheological performance of unsaturated polyester resin with bio-based reactive diluents: A comprehensive analysis of viscosity and thermomechanical properties - J. Grimalt; L. Frattini; P. Carreras; V. Fombuena (Polymer Testing, 2023)
Bio-based reactive diluents (RD) have been explored as alternative to styrene (STY) in unsaturated polyester resin (UPR). Among the different candidates, acrylated epoxidized soybean oil (AESO) and epoxidized linseed oil (ELO) stand out as triglyceride derivatives. Aditionally, methyl methacrylate (MMA), trimethylolpropane triacrylate (TMPTA) with acrylic functionality, limonene (LIM), and cinnamates (CINN), has been tested in different percentages. Firstly, their efficiency in viscosity reduction has been studied. Best results were obtained after the addition of MMA, LIM, and CINN at 5 wt%. These RD achieve a viscosity reduction of 48.9 %, 76.7 %, and 22.9 %, respectively, compared to the reference sample. The industrial utilization of CINN as RD is impeded by its reactivity, as has been evidenced by its prolonged reaction time (24 min) and low reaction enthalpy. The thermo-mechanical properties studied through flexural tests, Shore D hardness, Charpy's Impact test, and heat deflection temperature (HDT), show that the developed UPRs exhibit a decrease in resistant mechanical properties while doubling their ductility by using LIM and MMA as bio-based RD (1.88 and 2.15 kJ m−2, respectively). The HDT study results demonstrate a certain level of thermal stability when MMA is employed (56 °C), which is 15 % lower in the case of LIM. Therefore, it is observed that UPRs with bio-based RD exhibit balanced and improved thermo-mechanical properties in terms of ductility and strength, especially with the use of a 5 wt % of LIM and MMA.